Adverse Clinical and Economic Outcomes Attributable to Methicillin Resistance among Patients with Staphylococcus aureus Surgical Site Infection - Engemann, John J.; Carmeli, Yehuda; Cosgrove, Sara E.; Fowler, Vance G.; Bronstein, Melissa Z.; Trivette, Sharon L.; Briggs, Jane P.; Sexton, Daniel J.; Kaye, Keith S. (Clinical infectious diseases, 2003)
Data for 479 patients were analyzed to assess the impact of methicillin resistance on the outcomes of patients with Staphylococcus aureus surgical site infections (SSIs). Patients infected with methicillin-resistant S. aureus (MRSA) had a greater 90-day mortality rate than did patients infected with methicillin-susceptible S. aureus (MSSA; adjusted odds ratio, 3.4; 95% confidence interval, 1.5–7.2). Patients infected with MRSA had a greater duration of hospitalization after infection (median additional days, 5; P < .001), although this was not significant on multivariate analysis (P = .11). Median hospital charges were $29,455 for control subjects, $52,791 for patients with MSSA SSI, and $92,363 for patients with MRSA SSI (P < .001 for all group comparisons). Patients with MRSA SSI had a 1.19-fold increase in hospital charges (P = .03) and had mean attributable excess charges of $13,901 per SSI compared with patients who had MSSA SSIs. Methicillin resistance is independently associated with increased mortality and hospital charges among patients with S. aureus SSI.